Analisis Kompetensi Guru Fiqih Dalam Mengembangkan Keunikan Proses Pembelajaran Di Mts N 2 Wonogiri - Aurezia, Rhizma; Mukminin, Amir (Prgram Studi Pendidikan Agama Islam, 2025)
In the dynamics of contemporary education, teacher competence becomes a critical point in developing learning quality, especially in religious subjects like Fiqh. A profound concern about the professionalism of educators at MTs Negeri 2 Wonogiri prompted a comprehensive evaluative research. The complexity of educational challenges demands that teachers not merely meet minimal standards, but are capable of optimally transforming students' potential. Through field research using a qualitative approach, it was found that Fiqh teachers' competence is in the good category. Factors such as work ethic, educational qualifications, teaching experience, and environmental support play a significant role in shaping teacher professionalism. Each aspect is interconnected, forming a sustainable development ecosystem where teachers are not just teaching, but also dedicating themselves to guiding students to achieve their highest potential. This research provides a critical perspective on the importance of a holistic approach in teacher development, offering recommendations for policymakers to continuously develop a responsive and high-quality educational system.